Polly Diamond and the super, stunning, spectacular school fair - Kuipers, Alice, 1979- (Kuipers, Alice, 1979- Polly Diamond, 2019)
Today is the school book fair, which is very exciting for Polly Diamond, who loves books and writing, and who possesses a magic book which turns anything she writes into reality--but she also has to be careful because sometimes her book, Spell, does not quite understand a word and misinterpretations can be catastrophic.